STAYING ON TRACK: COMPLIANCE LEVELS AMONG ADULTS WITH DIABETES MELLITUS IN THE PHILIPPINES - Grace C. Arcamo, Jonah M. Novo; Naomi Datoy-Remolador (Chelonian Research Foundation, 2024)
Abstract: the study focused on Determining the compliance to treatment of Diabetes Mellitus patients. The study employed a normative descriptive research design. To gather the necessary data, a self-constructed questionnaire was developed, specifically tailored to describe the demographic and clinical characteristics of the adult diabetic population under study. To ensure the reliability and generalizability of the study results, the researcher employed simple random sampling in selecting the study participants. A total of 200 adult diabetic respondents were chosen from five clinics, ensuring a diverse and representative sample. The study highlights that compliance rates among diabetic respondents are influenced by various socio-demographic factors. While factors like age, gender, civil status, and the length of time diagnosed or on medication were found to have no significant impact on compliance, the study underscores the importance of understanding how education and income levels can affect medication adherence. Moreover, The study recommends adopting intervention strategies to improve compliance rates among diabetic patients. These strategies should consider not only socio-demographic factors but also the psycho-social and cultural aspects of patient care